Analysis of Al Qur’an Reading Skills for Junior High School Private - Mucharommah Sartika Ami; Ulul Hidayah (SCHOOLAR: Social and Literature Study in Education, 2024)
Muslim students need to have the skill of reading Al Qur’an from an early age so that they can understand and apply Islamic teachings properly and correctly. These skills need to be taught and trained in schools, for example through Islamic Religious Local Content in junior high school. Islamic Religious Local Content is an intra-curricular curriculum specifically launched for elementary and junior high schools by the government, including the regional government of Jombang Regency. State Junior High School (SMPN) 1 Tembelang is one of the schools that implements an Islamic Religious Local Content curriculum, but has never conducted an analysis of its students’ Al Qur’an reading skills. This research aims to analyze the skills of class VIII students at SMPN 1 Tembelang in reading Al Qur’an. The method used is descriptive with a qualitative research approach. Data collection was carried out through interviews, observation and documentation. Data analysis was carried out descriptively. The results of the research show that class VIII students at SMPN 1 Tembelang have fair Al Qur’an reading skills, both male and female students.